A Step towards national integration a movement to promote the creation of the Filipino writing system as a means to unite the Filipino nation - Meren, Daniella C.
What does it mean for a country to be united? What does it mean when they say a strong nation? The answer is simple, "National Integration". It is the willingness of the people in a nation to give their resources for the betterment of their fellowmen despite the individual social institutions they belong in. A unified nation then is one that contains at least majority if not all of the people, that places the priority in what is best for the whole nation community first and not just on the smaller groups they belong in. If that's the case then is the Philippines considered a unified nation? By national integration's definition, no, the Philippines is not. What can be dome in order to attain nationwide unity then? Yet again the answer is uncomplicated. If there is a desire to unite then the solution would be to provide a unifying medium that the people would find a connection with. In the case of a unifying medium, a nationwide agreement on one Lingua Franca would be ideal but as the current situation in the Philippines makes such a feat next to impossible. The next candidate then was the writing system. A writing system that belongs only to these people in the Filipino nation. One that the people are certain to approve, one that doesn't exclude any groups that belongs in the Philippine culture, and this one simple thing that the Philippine needs in order to become a unified nation, is a new writing system.